Search engine advertising : buying your way to the top to increase sales - Lee, Kevin (Voices that matter., 2009)
"A remarkable book that eases you into the important world of search engine advertising. Read it before your competitors do!"--Danny Sullivan, Editor SearchEngineWatch.com Nothing delivers high-quality traffic like the search engines, but if you're not showing up prominently in the results for your desired keywords, that means your competition is. The way to gain control and maximize profit is to take advantage of paid search results. Paid search engine listings can deliver site visitors who want to buy what you sell. And they can pinpoint exactly the right landing pages using not only keywords, but also geography, time of day, and more. With a little education and pre-planning, any company can launch a profitable search engine advertising program. Key features in this book include learning how to: - Buy top positions on the major search engines profitably - Transform poor ad copy into ads that deliver results - Increase visitor-to-buyer conversions - Begin paid search advertising now, even if you're a novice - Use advanced techniques to evaluate and improve your results - Leverage successes from Google into Yahoo, Microsoft, and more - Leave the unprofitable clicks to your competition while grabbing the most profitable ones